2007
DOI: 10.1002/adsc.200700242
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Pincer Complex‐Catalyzed Condensation of Sulfonimines and Isocyanoacetate to Imidazoline Derivatives. Dependence of the Stereoselectivity on the Ligand Effects

Abstract: Palladium-catalyzed condensation reactions of sulfonimines with isocyanoacetate were performed using various PCP, SCS, SeCSe and NCN pincer complexes as catalysts. The reactions proceeded rapidly (2 h) at room temperature using only 1 mol % pincer complex catalyst without any additives. The electron-deficient and relatively bulky PCP complex provides imidazoline derivatives with a very high syn diastereoselectivity. The applied PCP catalyst proved to be very robust under the applied reaction conditions, as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 58 publications
0
42
0
1
Order By: Relevance
“…The applied chemicals were obtained from commercial sources or synthesized according to literature procedures: 1d, [42] 1g, [43] 1i, [44] 3a [6] and 3b. [45] General Procedure…”
Section: Methodsmentioning
confidence: 99%
“…The applied chemicals were obtained from commercial sources or synthesized according to literature procedures: 1d, [42] 1g, [43] 1i, [44] 3a [6] and 3b. [45] General Procedure…”
Section: Methodsmentioning
confidence: 99%
“…Crystal data [Co(C 30 Data collection: SMART (Bruker, 1997); cell refinement: SAINT (Bruker, 1997); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEPIII (Burnett & Johnson, 1996) and ORTEP-3 for Windows (Farrugia, 1997); software used to prepare material for publication: SHELXTL (Sheldrick, 2008 (Boom & Milstein, 2003;Bedford et al, 2006;Gomez-Benitez et al, 2006;Aydin et al, 2007;Kimura & Uozumi, 2006). We previouly reported that the central sp3 C-H bond of (Ph 2 POCH 2 ) 2 CH 2 could be activated by Co(PMe 3 ) 4 to afford metallated 'PCP' pincer compounds at room temperature (Xu et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For uses of 'PCP' pincer complexes, see: Boom & Milstein (2003); Bedford et al (2006); Gomez-Benitez et al (2006); Aydin et al (2007); Kimura & Uozumi (2006); Xu et al (2009).…”
Section: Related Literaturementioning
confidence: 98%
“…Mechanistic studies show that the isonitrile binds particularly strongly to the metal center, implying that the palladium-isonitrile bond is best considered as a covalent bond. [32] Deprotonation of the metal-bound isonitrile is facile and does not necessarily require added base to form the enolate 61 . The slow step of the pincer-catalyzed aldol condensation is the attack of the coordinated isonitrile enolate 61 on the aldehyde or imine.…”
Section: Aldol-type Condensationsmentioning
confidence: 99%